Tempo di viaggio - Tarkovskij, Andrej Arsen'evic; Guerra, Tonino; Tovoli, Luciano (Artificial Eye, 2002)
Andrei Tarkovski and Tonino Guerra, in their search for the location of "Nostalghia" (1983), give an account of their extraordinary "Travel across Italy". Guerra guides Tarkovski through Italy's most traditional beauties. Tarkovski, amazed and disenchanted, is intent in his search of a more secret and inner Country which, perhaps, exists only in his imagination as an artist. In the end he will find what he is looking for in the desolate countryside of Central Italy and in the medieval villages around Sienna. Throughout this trip he is constantly urged by Tonino Guerra to reflect on his work and to think back on his experience as a film-maker and a poet. [www.festival-cannes.com]